Local Administration Organizations in the Southern Border Provinces’Perceptions of and Responses to Area-Based Tobacco Integrative Control in Legal and Social Dimensions: A Case Study of Local Administrative Organizations in Raman District, Yala Province: การรับรู้และการตอบสนองบทบาทขององค์กรปกครองส่วนท้องถิ่นในจังหวัดชายแดนใต้ต่อการควบคุมยาสูบแบบบูรณาการมิติกฎหมายและมิติสังคมในระดับพื้นที่: กรณีศึกษา องค์กรปกครองส่วนท้องถิ่นในพื้นที่อำเภอรามัน จังหวัดยะลา - Khumphiranont, Siriluk; Nunkliang, Supreeya; Makeng, Isayas; Latekeh, Nuriya; Suwanruksa, Tongchan (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This research studied things towards integrative tobacco control which were local administrative organizations’roles, perceptions of and attitudes, their operational effectiveness and obstacles encountered by stakeholders who got involved in, and the development for a cooperative network in building processes among stakeholders being in driving tobacco control in boundary area in terms of legal and social dimensions. A quantitative research method was mainly utilized in this research. By applying two sets of questionnaires for each two sampling groups (segmenting groups) in total of 237 people, an overall reliability coefficient alpha was .90 and .87. The other qualitative research method was taken by a group discussion and a workshop. Percentages, frequencies, arithmetic means and standard deviation were applied for logical analysis in qualitative data. The results were as follows: In overall, the quantitative results conducted from attitudes of two segment groups towards integrative tobacco control was at a medium layer. Which included responsiveness of local administrative organizations’ roles, acknowledges of both policy and Tobacco Act, perceptions of driving problems' situation and the impact on tobacco of their functional effectiveness and problems obtained by stakeholders. Developments of cooperative network building among local administration organizations and stakeholders in tobacco control contextually varied. There were several frameworks of processes. Activities which drived public policies for health, created an environment that was conducive to health, strengthened communities, and improved health care system. However, approaches for cooperation promotion in network groups for tobacco control depended particularly on supply chain. In addition, the situation of tobacco problems was found at various meeting sources. There were many forms of tobacco control activities. The planning pilot activities focused on community and environmental creation.